2020
DOI: 10.1016/j.jep.2019.112352
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm inhibiting properties of compounds from the leaves of Warburgia ugandensis Sprague subsp ugandensis against Candida and staphylococcal biofilms

Abstract: Warburgia ugandensis Sprague subspecies ugandensis is a plant widely distributed in Eastern, Central and Southern Africa. In humans, it is used to treat respiratory infections, tooth aches, malaria, skin infections, venereal diseases, diarrhea, fevers and aches. Aim of the studyThis study aims to identify the bioactive compounds against clinically important biofilm-forming strains of Candida and staphylococci that are responsible for tissue and implanted device-related infections. MethodsUsing a bioassay-guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…According to the European Committee on Antimicrobial Susceptibility Testing (EUCAST), the antifungal clinical breakpoints are between 0.001 mg/L and 16 mg/L [ 60 ]. Using EUCAST guidelines in this review, the most active compounds that inhibit (>50%) Candida biofilm formation are lichochalcone A (from 0.2 mg/L) [ 61 ], thymol (from 3.12 mg/L) [ 26 ], dioscin (from 3.9 mg/L) [ 31 ], baicalein (from 4 mg/L) [ 62 ], warburganal (4.5 mg/L) [ 52 ], pterostilbene, waltheriones and riccardin D (both from 8 mg/L) [ 63 , 64 , 65 ], polygodial (10.8 mg/L) [ 52 ], cannabidiol and eugenol (both from 12.5 mg/L) [ 58 , 66 ], and ivalin (15.4 mg/L) [ 67 ]. It is interesting that monotherpenes, which represent the highest percentage of substances listed in Table 2 , are not the most active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…According to the European Committee on Antimicrobial Susceptibility Testing (EUCAST), the antifungal clinical breakpoints are between 0.001 mg/L and 16 mg/L [ 60 ]. Using EUCAST guidelines in this review, the most active compounds that inhibit (>50%) Candida biofilm formation are lichochalcone A (from 0.2 mg/L) [ 61 ], thymol (from 3.12 mg/L) [ 26 ], dioscin (from 3.9 mg/L) [ 31 ], baicalein (from 4 mg/L) [ 62 ], warburganal (4.5 mg/L) [ 52 ], pterostilbene, waltheriones and riccardin D (both from 8 mg/L) [ 63 , 64 , 65 ], polygodial (10.8 mg/L) [ 52 ], cannabidiol and eugenol (both from 12.5 mg/L) [ 58 , 66 ], and ivalin (15.4 mg/L) [ 67 ]. It is interesting that monotherpenes, which represent the highest percentage of substances listed in Table 2 , are not the most active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the same year, Lemos et al [ 159 ] demonstrated that Sc, at its MIC (50 µg/mL), was able to reduce the preformed biofilms of a resistant C. tropicalis strain in 68.2%, and to inhibit the biofilm formation. Kipanga et al [ 160 ] showed that the drimane sesquiterpene dialdehydes warburganal and polygodial, obtained from Warburgia ugandensis Sprague (Canellaceae), inhibited C. albicans biofilm formation with MBIC 50 of 4.5 and 10.8 µg/mL, respectively, and with MBIC 50 of 49.1 and 50.6 µg/mL, respectively, against C. glabrata . Regarding biofilm eradication, warburganal and polygodial showed MBEC 50 of 16.4 and 16.0 µg/ml, respectively, against C. albicans but did not inhibit C. glabrata biofilm eradication.…”
Section: Reported Antibiofilm Activities Of Pure Natural Compoundsmentioning
confidence: 99%
“…Apart from the anti-feedant activity against a number of pests [ 1 , 2 , 3 ], polygodial ( Figure 1 ) has been reported to possess biological activities such as antifungal [ 4 , 5 , 6 ], antibacterial [ 7 ], anti-tumor [ 8 ], larvicidal [ 9 ], antihelminthic [ 10 ], antifouling [ 11 ], anti-inflammatory [ 12 ], analgesic [ 13 ], antitrypanosomal, and antileishmanial activities [ 14 ]. As a bioactive constituent, it is produced in several plants of the Canellaceae [ 1 ], Polygonaceae [ 15 ], and Winteraceae [ 16 ] families, as well as in marine animals such as sponges and molluscs [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a bioactive constituent, it is produced in several plants of the Canellaceae [ 1 ], Polygonaceae [ 15 ], and Winteraceae [ 16 ] families, as well as in marine animals such as sponges and molluscs [ 17 , 18 ]. Recently, we isolated polygodial from Warburgia ugandensis Sprague subspecies ugandensis (Canellaceae) and showed its activity against Candida albicans [ 6 ]. Specifically, we showed that low concentrations of polygodial are not only active against the planktonic forms of C. albicans , but that the compound is also active against its biofilm forms (biofilm inhibiting concentration: BIC 50 =10.8 ± 5 μg/mL); which are a major menace to public health due to their increased resistance to currently available antifungals [ 19 ].…”
Section: Introductionmentioning
confidence: 99%